2016
DOI: 10.14507/epaa.24.2441
|View full text |Cite
|
Sign up to set email alerts
|

Public expenditures and the production of education

Abstract: The relationship between public education expenditures and student outcomes remains an important concern for policy analysts, educational administrators, and the public at large. While previous studies have failed to identify a consistent relationship between public investments in education and positive student outcomes, most analyses have not accounted for the different educational goals associated with various instructional expenditure categories. This study builds on prior research by using Pennsylvania’s p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…This persistent poor performance is particularly noticeable in the area of strategic management (Naicker & Ncokwana, 2016). According to Neely & Diebold (2016), a common suggestion to address school performance is adequate funding; however, policymakers and educators do not seem to believe that adequate resources will improve school performance. Neely & Diebold (2016) have shown that the concept of resourcing is central to many funding models.…”
Section: Background To the Research Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…This persistent poor performance is particularly noticeable in the area of strategic management (Naicker & Ncokwana, 2016). According to Neely & Diebold (2016), a common suggestion to address school performance is adequate funding; however, policymakers and educators do not seem to believe that adequate resources will improve school performance. Neely & Diebold (2016) have shown that the concept of resourcing is central to many funding models.…”
Section: Background To the Research Problemmentioning
confidence: 99%
“…According to Neely & Diebold (2016), a common suggestion to address school performance is adequate funding; however, policymakers and educators do not seem to believe that adequate resources will improve school performance. Neely & Diebold (2016) have shown that the concept of resourcing is central to many funding models. One might assume that the concept of resourcing is central to the education strategies of the South African government.…”
Section: Background To the Research Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have evidenced an association between variations of the districts in educational resources with the variations of the districts in student outcomes (Fowler & Walberg, 1991;Sander, 1993). Literature on education production function in the USA (e.g., Neely & Diebold, 2016), which looks at the association between input and student outcome, has long found a positive relationship between education spending at district level and achievement, albeit not consistent across studies (Hanushek, 1989). While spending as input may also be considered an index of quality of education (Rizzuto & Wachtel, 1980), the socioeconomic status of the districts also has an effect on the learning outcomes (Fowler & Walberg, 1991).…”
Section: District Level Variablesmentioning
confidence: 99%